Characterization of a pathogenic gain-of-function mutation in the N-terminal domain of STAT1 which is reported to be associated with eosinophilic esophagitis - Kristin Annawald; Anke Gregus; Oliver Wirths; Thomas Meyer (Cell Communication and Signaling)
Abstract The pathophysiology of eosinophilic esophagitis (EoE), a chronic allergic disease characterized by eosinophilic infiltration of the esophageal mucosa, is largely unknown. Recently, a case report described a gain-of-function (GOF) mutation in the STAT1 (signal transducer and activator of transcription 1) protein (D65A) to be associated with this disease. In the present paper, we investigated in more detail the molecular mechanisms of this missense mutation and, in addition, characterized a second aspartic acid-to-alanine substitution (D66A) in the N-terminal domain of STAT1. Results showed that, upon stimulation of cells with cytokines, the two mutants had increased levels of tyrosine phosphorylation compared to the wild-type (WT) protein. The altered phosphorylation kinetics led to an elevated and prolonged phase of nuclear accumulation, which was in line with an increased concentration of DNA-bound complexes observed by means of electrophoretic mobility shift assays. However, the dissociation rate from a single high-affinity DNA-binding site did not differ between the WT and the two mutants. A promoter-specific higher transcriptional activation was observed for reporter gene constructs and the majority of the tested endogenous STAT1 target genes. In summary, the two N-terminal point mutations showed characteristic features of a GOF phenotype, as indicated by a gene-specific, rather than a global upregulation of cytokine-driven gene expression. A model is proposed suggesting that the equilibrium between antiparallel, tetrameric complexes and parallel dimer complexes is shifted to the transcriptionally active latter ones as the underlying mechanistic basis of these N-terminal STAT1 mutations.